THE INFLUENCE OF LEADERSHIP, COMMUNICATION AND WORK ATTITUDES WITH ORGANIZATIONAL COMMITMENT AS INTERVENING VARIABLES ON THE PERFORMANCE OF REGIONAL SECRETARIAT EMPLOYEES OF TANJUNGPINANG CITY - Jerry Setiawan, Ikram; Muammar Khaddafi; Indrayani, Indrayani; Satriawan, Bambang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine the effect of leadership, communication and work attitude with organizational commitment as a mediating variable on the performance of Tanjungpinang City Regional Secretariat employees. The hypothesis put forward Leadership affects Performance, Communication Affects Performance, Work Attitude affects Performance, Organizational Commitment affects Performance, Leadership influences Organizational Commitment, Communication Affects Organizational Commitment, Work Attitude influences Organizational Commitment, Leadership influences Performance through Organizational Commitment, Communication influences Performance through Organizational Commitment , Work Attitudes Affect Performance through Organizational Commitment. The sample in this study were all employees at the Tanjungpinang City Regional Secretariat Office with a total of 116 respondents. The data obtained were analyzed using data analysis techniques with the help of PLS software. The results showed that leadership had no significant positive effect on performance. Communication has no significant positive effect on performance. Work attitude has a significant positive effect on performance. Organizational Commitment influences Performance significant positive. Leadership Affects Significantly Positive Organizational Commitment. Communicationinfluence Organizational Commitment significantly positive. Work attitude has a significant positive effect on Organizational Commitment. Leadership Influence on Performance is mediated by Significant Positive Organizational Commitment, Communication Influence on Performance is mediated by Significantly Positive Organizational Commitment. Work Attitudes influence Performance mediated by Organizational Commitment significantly positive.